Cover Feature: Photoinduced Water Oxidation in Chitosan Nanostructures Containing Covalently Linked RuII Chromophores and Encapsulated Iridium Oxide Nanoparticles (Chem. Eur. J. 68/2021). Issue 68 (4th October 2021) - La Ganga, Giuseppina; Puntoriero, Fausto; Fazio, Enza; Natali, Mirco; Nastasi, Francesco; Santoro, Antonio; Galletta, Maurilio; Campagna, Sebastiano
Abstract : Fiber gels made of Ru(bpy)3 2+ ‐decorated chitosan and incorporating IrO2 nanoparticles (see SEM image in the background) can effectively perform photoinduced water oxidation with better performance than isolated components. In particular, a significantly higher quantum yield for water oxidation and a better stability of the system are reported. More information can be found in the Full Paper by G. La Ganga, S. Campagna et al. (DOI: 10.1002/chem.202102032 ).